2017
DOI: 10.3389/fmicb.2017.00673
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Arabidopsis thaliana in Response to Plasmodiophora brassicae during Early Infection

Abstract: Clubroot disease is a serious threat to cruciferous plants worldwide, especially to oilseed rape. However, knowledge on pathogenic molecular mechanisms and host interaction is limited. We presume that the recognition between Arabidopsis thaliana and Plasmodiophora brassicae occurs at the early stage of infection and within a relatively short period. In this study, we demonstrated changes on gene expression and pathways in A. thaliana during early infection with P. brassicae using transcriptome analysis. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 61 publications
(84 reference statements)
1
51
0
Order By: Relevance
“…Transcriptome sequencing can provide information regarding the gene content of a species and can complement genome sequencing approaches [21]. RNA sequencing (RNA-Seq) has been applied as a tool for transcriptome analysis in many species, such as Arabidopsis thaliana, [22], Brassica spp. [23], rice [24], maize [25], and sugarcane [21].…”
mentioning
confidence: 99%
“…Transcriptome sequencing can provide information regarding the gene content of a species and can complement genome sequencing approaches [21]. RNA sequencing (RNA-Seq) has been applied as a tool for transcriptome analysis in many species, such as Arabidopsis thaliana, [22], Brassica spp. [23], rice [24], maize [25], and sugarcane [21].…”
mentioning
confidence: 99%
“…El Modafar and El Boustani [43] suggested that lignin contents are associated with the date palm resistance to F. oxysporum. Lignin accumulation regulates the resistance of Arabidopsis to P. brassicae [37]. Our results showed that lignin began to accumulate at the early infection stage to enhance resistance to Foc, suggesting that the lignin biosynthesis may be a crucial component of 'Brazilian' defense difference in response to Foc1 and Foc4 infection.…”
Section: Gens Involved In Lignin Biosynthesis Pathwaymentioning
confidence: 66%
“…Flavonoids, a group of secondary metabolites, play a significant role in plant defense against pathogens [35]. Siemens et al [36] and Zhao et al [37] indicated that numerous genes involved in flavonoid pathway were enhanced expression in Arabidopsis after infection with P.brassicae, as a consequence, the content of flavonoid was accumulated in clubroot galls of Arabidopsis. Only two CHS genes and a LDOX gene involved in flavonoid biosynthesis were up-regulated in the roots of the resistant banana variety 'Guijiao 9' during incompatible banana-Foc4 interaction (Sun et al, 2019).…”
Section: Flavonoid Biosynthesis Pathway Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some researchers put forward that the early infection also played an important role. Both Arabidopsis and Chinese cabbage were carried out the study on the mechanisms of early infection (Chen et al, 2015;Zhao et al, 2017), which showed that part of pathways or proteins identified in the middle or late phase also could be detected in the early infection stage. In this study, we investigated the response of B. napus accessions with different resistance levels at the early stage of P. brassicae infection, which could provide more information about the mechanisms of early infection of Brassica crops to P. brassicae.…”
Section: Discussionmentioning
confidence: 99%